MUSICAL DECORATION AND THEIR PERFORMANCE METHODS - Abduraimov Sherzod Zakir ugli (Bright Mind Publishing, 2025)
This article discusses the artistic features of the performance of the kashqar rubabi in Central Asia, in particular in Uzbekistan, and the methods of their performance. The author emphasizes the importance of musical decorations, melismas and khachirims in the art of music and performance, and also shows that the perfect performance of kashqar rubabi works requires high skill, musical thinking and technical mastery. The article emphasizes the performance technique, the importance of sound quality, artistic expression of music and the specific characteristics of instruments. It discusses the promotion of Uzbek music in the international arena, as well as the important role that the works of composers played in the development of kashqar rubabi performance. This article helps to understand the future of kashqar rubabi performance and its significance as a musical heritage.
Keywords: composer, song, music, character, composer, people, ornament, performance, skill, performance, work, pedagogy, instrument.